PRODUCTIVITY OF FISHERIES GOMBANG IN VILLAGE SIALANG PASUNG RANGSANG BARAT DISTRICT MERANTI ISLANDS REGENCY RIAU PROVINCE - Kurniawan Kurniawan; Arthur Brown; Bustari Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT One of the fishing gear used by fisherman in Sialang Pasung Village is the gombang fishing gear. The purpose of this study is to know the fishing gear productivity gombang in Sialang Pasung Village. The research was conducted in July 2018. Using sampling and observations method. During the study obtained the total catches of 108,713 kg. Catches during the study was anchovy (Clupeodes lile) which was the main catch average 25060 gr. fishing gear productivity during the study was 26586 gr with actual fishing time of 0.1409 gr / m3.t which happened on the third day. Keywords: Sialang Pasung Village, Gombang, Productivity dan Catch Result